Analysis of drug-induced hand-foot syndrome using a spontaneous reporting system database - Yu Yoshida; Sayaka Sasaoka; Mizuki Tanaka; Kiyoka Matsumoto; Misaki Inoue; Riko Satake; Kazuyo Shimada; Ririka Mukai; Takaaki Suzuki; Mari Iwata; Fumiya Goto; Takayuki Mori; et al. (SAGE Publishing, 2022)
Purpose: The aim of our study was to assess the clinical features of hand-foot syndrome (HFS) associated with certain systemic chemotherapeutic drugs in a real-world setting using the Japanese Adverse Drug Event Report (JADER) database. Methods: HFS was defined using the preferred terms from the Medical Dictionary for Regulatory Activities. We used several indices, such as the reporting odds ratios (RORs) at 95% confidence interval (CI), the time-to-onset profile of HFS, and cluster analysis. Results: Of 646,779 reports (submission period: April 2004 to September 2020), 1814 reported HFS events. The RORs (95% CI) for axitinib, capecitabine, lapatinib, regorafenib, sorafenib, and sunitinib were 14.9 (11.1-20.1), 54.6 (49.2-60.6), 130.4 (110.7-153.6), 63.3 (55.2-72.6), 29.0 (25.8-32.7), and 13.9 (11.7-16.5), respectively. The analysis of time-to-onset profiles revealed that the median values (interquartile range: 25.0-75.0%) of drug-induced HFS caused by capecitabine, cisplatin, docetaxel, everolimus, regorafenib, sorafenib, and trastuzumab were 21.0 (13.0-42.0), 15.0 (10.0-82.0), 6.0 (3.0-25.0), 86.5 (67.0-90.5), 9.0 (6.0-14.0), 9.0 (6.0-14.0), and 70.0 (15.0-189.0) days, respectively. The number of clusters was set to 4. Among these, one cluster, which included capecitabine, regorafenib, and lapatinib, exhibited a higher reporting ratio and ROR of drug-induced HFS than other drugs. Conclusions: The RORs and results of time-to-onset analysis obtained in this study indicated the potential risk of HFS associated with chemotherapeutic drugs. Our results suggest that health care professionals must be aware of the potential onset of drug-induced HFS with docetaxel, regorafenib, and sorafenib for at least 4 weeks; therefore, careful observation is recommended. Plain Language Summary Elucidation of the relationship between cancer drugs and risk of hand-foot syndrome Purpose: Hand-foot syndrome (HFS) is an adverse effect of some cancer drugs, which is characterized by symptoms such as redness, swelling, blistering, and pain in the area of palms and soles. HFS reduces the quality of life of patients and can sometimes interfere with anticancer treatment plans. It is important to understand the clinical manifestations of HFS and gain knowledge that will allow for early intervention by clinicians. Methods: In this study, we used a large-scale side effect database of real-world cases for a comprehensive investigation of anticancer-drug-induced HFS. The database contained 646,779 adverse event reports from April 2004 to September 2020; among which, we identified 1814 HFS events. Using these data, we could obtain information on the relationship between 19 types of anticancer drugs and HFS, and the onset time of HFS and HFS prognosis related to each anticancer drug. Results: Our results suggest that clinicians should monitor the risk of HFS with docetaxel, regorafenib, and sorafenib for at least the first 4 weeks after drug administration. Conclusion: These findings are crucial for improving the management of the adverse effects caused by anticancer drugs.